PENGARUH PENGGUNAAN LEMAK NABATI TERHADAP KUALITAS CHIFFON CAKE - Nabilah, Nurli; Syarif, Wirnelis; Elida, Elida (Journal of Home Economics and Tourism, 2017)
This study aims to see the effect of vegetable fats use of palm oil, corn oil, soybean oil and coconut oil to the quality of chiffon cake. The type of this research is experiment with complete randomized design method. The X variables are palm oil, corn oil, soybean oil and coconut oil, and Y variables are external quality (volume, shape and color), and internal quality (aroma, texture and taste) of chiffon cake. Source of data obtained directly from 15 panelists by filling the format of organoleptic test. Data analysis was done by Varian Analysis (ANAVA), if Fcount> Ftable then continued with Duncan test. The results showed that there was a real effect on the quality (shape and sweetness) while for the quality of volume, color, aroma, texture and taste of vegetable fat no significant effect.Keywords: Vegetable Fat, Quality Chiffon Cake